MANAGEMENT OF ADRENAL INSUFFICIENCY DURING RAMADAN FASTING : A SURVEY OF MALAYSIAN ENDOCRINOLOGISTS - Hee, Nicholas Ken Yoong; Lim, Quan Hziung; Paramasivam, Sharmila; Lim, Lee Ling; Chan, Siew Pheng; Vethakkan, Shireene; Vethakkan, Shireene; Ratnasingam, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The management of adrenal insufficiency (AI) in Muslim patients fasting during Ramadan poses a challenge for endocrinologists. As the afternoon dose of hydrocortisone needs to be omitted, most guidelines recommend converting twice daily hydrocortisone to once daily, dose equivalent prednisolone, but this is not standard practice. METHODOLOGY An online survey was disseminated amongst all endocrinologists and endocrinology trainees in Malaysia. https://forms.gle/XR629nBjMu4XWM6HA. RESULT There was a total of 91 respondents, consisting of adult endocrinologists (58.2%) and endocrinology trainees (41.8%). Among these physicians, 84.6% treated more than 10 patients with AI in a year, with 34.1% of respondents estimating that more than half of their patients were Muslim. Hydrocortisone was the most common formulation (91.2%) during non-fasting months. According to 70.3% of respondents, Ramadan would have a definite effect on glucocorticoid replacement therapy. Respondents detected fatigue as the most common symptom encountered by AI patients during Ramadan (92.3%), followed by dizziness (90.1%), hypoglycaemia (85.7%), hypotension (81.3%), nausea (74.7%) and weight loss (45.1%). Late afternoon was considered the most likely time for symptoms of glucocorticoid under-replacement to occur by 56% of respondents. A vast majority (90.1%) confirmed that they provide specific recommendations during Ramadan fasting. There was a difference in practice amongst those who provided recommendations, with 53.0% of respondents recommending once daily prednisolone at sahur while the remainder opting for twice daily hydrocortisone given at sahur and second dose at iftar. The rate of prescribing prednisolone was different among endocrinologists and trainees (42.6% vs 66.7%, p=0.03). When comparing the type of practice— public hospital, academic hospital or private practice, prednisolone prescription rate was 51.8%, 78.6% and 30.8% respectively (p=0.05). CONCLUSION There is significant variation in practice amongst the endocrinology fraternity in Malaysia when prescribing glucocorticoids during Ramadan. There is a crucial, urgent need for development of local guidelines on glucocorticoid replacement for fasting during Ramadan for Muslims with AI.